Scientific Leadership - Niemantsverdriet, J. W. (Hans); Felderhof, Jan-Karel (De Gruyter Textbook, 2017)
Modern Science is teamwork. But how can young academics go from being a productive member of a scientific team to leading their own? Entry level positions for PhDs in Science often require the infamous "people skills". The authors aim to equip young academics with the right ideas and strategies for their scientific leadership development. Become a successful leader not with tricks, but with an inspiring and straightforward vision and mission, the correct mindset, and effective teamwork.